PROBLEMS IN TAXATION IN NIGERIA: A COMPARATIVE ANALYSIS (1974)
Working on a comparative basis, the objective here is to review certain aspects of Nigerian taxation. While the primary concern is with legal problems, an analysis of tax principles in the abstract is thought to be of limited value unless account is taken of the underlying economic problems which they are designed to regulate. Hence, wherever possible, legal principles are examined in the context of the country’s programme for economic development and the role of foreign capital and technology in fulfilling that objective. The introductory chapter sets out the aims of this thesis in more detail and emphasizes the inter-disciplinary approach. Also highlighted, are the division of taxing powers within the federal set up and the legal framework for economic activity. Chapter Two, a thorough analysis of the charging provisions, establishes the essential philosophy behind the general scheme of taxation Subsequent discussion is based on two principles - liability on all "source” income and on "remittances." In Chapter Three, problems relating to the taxation of business income are considered. Namely, the concept of "carrying on" business in Nigeria — the determination of taxable profits - accounting and related problems - allocation of income and expense between related entities - and the tax treatment of losses and a number of special trades (viz., shipping, insurance and the import and export trade). Chapter Four deals with the taxation of employment and professional income. Some of the areas explored include valuation of benefits in kind - expenses - and the machinery for assessment and collection. The tax treatment of investment income (i.e. interest, royalties and dividends) is reviewed in Chapter Five - especially as regards the "source principle and the inflow and outflow of foreign investments. Nigeria’s tax treaties are examined in Chapters Six, Seven and Eight. This takes place in the light of the OECD Draft Double Taxation Convention on Income and Capital. Cognisance is also taken of recent developments on the international scene. A resume of the principal findings and recommendations is offered in Chapter Nine. Although considerable thought was given to the taxation of oil companies, material on this subject had to be dropped at the last minute because of the present confused state of the international oil industry and its direct influence on Nigeria’s internal law. References in the text to our proposed chapter on Oil Company Taxation must, therefore, be disregarded. (Please see note at page 610 infra.) This thesis states the law as at 30th September 1974